2006
DOI: 10.1038/sj.pcan.4500914
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the risk of prostate cancer: the role of diabetes treatment and complications

Abstract: Epidemiologic evidence suggests diabetic men have a slightly lower prostate cancer risk than nondiabetic men. We examined this association in a prospective cohort study of 35 239 men, 50-76 years old, in Washington State who completed a baseline questionnaire between 2000 and 2002. Incident prostate cancers as of 31 December 2004 were identified through the SEER registry. Diabetic men had a slightly lower risk of prostate cancer than non-diabetic men (hazard ratio (HR) 0.83, 95% confidence interval (CI) 0.64-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
4
17
1
1
Order By: Relevance
“…It is not clear to what extent a PSA reduction of 15% corresponds with a prostate cancer risk reduction of 16% and how much delay there is between change in PSA levels and changes in prostate cancer risk. However, as both PSA and prostate cancer risk tend to change in the same direction in diabetic patients, i.e., both are reduced, and two studies (24,25) showed a prostate cancer risk reduction in diabetic men using insulin (À36% to À51%), which was comparable with our PSA reduction in these men (À40%), a recommendation to adjust PSA values for diabetes to improve prostate cancer detection does not seem to be warranted with current knowledge. Nevertheless, data that differentiate prostate cancer risk in diabetic men according to the severity of the disease are still rare and thus needed to assess the association of PSA and prostate cancer risk reduction.…”
Section: Discussionsupporting
confidence: 71%
“…It is not clear to what extent a PSA reduction of 15% corresponds with a prostate cancer risk reduction of 16% and how much delay there is between change in PSA levels and changes in prostate cancer risk. However, as both PSA and prostate cancer risk tend to change in the same direction in diabetic patients, i.e., both are reduced, and two studies (24,25) showed a prostate cancer risk reduction in diabetic men using insulin (À36% to À51%), which was comparable with our PSA reduction in these men (À40%), a recommendation to adjust PSA values for diabetes to improve prostate cancer detection does not seem to be warranted with current knowledge. Nevertheless, data that differentiate prostate cancer risk in diabetic men according to the severity of the disease are still rare and thus needed to assess the association of PSA and prostate cancer risk reduction.…”
Section: Discussionsupporting
confidence: 71%
“…[20][21][22] Indeed, many studies have reported an inverse association between diabetes and PCa risk. [2][3][4][5][6][7][9][10][11] However, diabetes is also linked to lower serum PSA. 13,14 Thus, in clinical practice where PSA screening drives recommendations for biopsy and, hence, PCa detection, an alternative explanation for the attenuated PCa risk reported by many but not all studies is that lower PSA in diabetics leads to fewer biopsies and, consequently, to less frequent diagnosis of extant cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported decreased PCa risk among diabetics whereas others found either no protective effect or an elevated risk. [1][2][3][4][5][6][7][8][9][10][11][12] Two recent meta-analyses, one examining studies from 1971-2002 and the other extending this review to 2005, both concluded diabetes is inversely associated with PCa risk. 2,3 However, only a minor risk reduction (RR ¼ 0.91, 95% confidence interval (CI) 0.86-0.96) was noted in the first meta-analysis whereas, in the second, diabetes appeared protective only among studies conducted after widespread adoption of PSA screening (RR ¼ 0.73, 95% CI 0.64-0.83).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 13 relevant studies on the association between DM and PCa have been published since 2006, consisting of 8 prospective studies (Calton et al, 2007;Velicer et al, 2007;Leitzmann et al, 2008;Kasper et al, 2009;Wallstrom et al, 2009;Waters et al, 2009;Li et al, 2010;Lee et al, 2012) and 5 retrospective ones (Gong et al, 2006;Pierce et al, 2008;Baradaran et al, 2009;Pelucchi et al, 2011;Turner et al, 2011). With more than 30,000 additional PCa cases, we aimed to re-analyze this relationship further by conducting an updated detailed meta-analysis with focusing on the effect of time, namely the duration since DM was diagnosed and the age of patient when DM was diagnosed.…”
Section: Diabetes Mellitus Reduces Prostate Cancer Risk -No Function mentioning
confidence: 99%